Comparative analysis of two concurrent training proposals on physical fitness in overweight adult women - López , Mario (2025)
Introduction: Concurrent training (CT) is an effective tool to improve physical fitness (PF) and body composition (BC) in individuals with overweight. Objective: The main objective of this study was to compare whether there were significant differences between two CT groups in different PF-related variables. Results: Although no significant differences were found when comparing both groups in any of the analyzed variables, improvements were observed in all variables from the beginning of the intervention in both groups. The intra-session CT group showed greater changes from baseline in all variables, except for body mass index (BMI), maximal strength in dumbbell chest press, and upper body flexibility, where greater benefits were obtained in the intra-mesocycle CT group. Conclusions: It is concluded that both training programs may improve PF in overweight women with a moderate level of PA after a 6-week intervention period using this training methodology, with intra-session CT being potentially more beneficial for this population when the objective is the general improvement of PF.Keywords: combined training, endurance, overweight, physical exercise, strength